A wave absorbing material, a wave absorbing tube sleeve using the same and a preparation method thereof
By combining spherical soft magnetic powder with sheet-shaped soft magnetic powder in a specific proportion, and through specific kneading and extrusion processes, an absorbent material with high magnetic permeability was prepared, which solved the problems of poor fluidity and insufficient magnetic permeability in the preparation process of existing absorbent materials, and achieved efficient anti-electromagnetic interference effect.
Patent Information
- Application Number
- CN202411329416.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-09-24
AI Technical Summary
There is an electromagnetic interference problem between existing electronic products, and the existing wave absorbing materials have poor fluidity and insufficient magnetic permeability during the preparation process, making it difficult to effectively resist electromagnetic interference.
Spherical soft magnetic powder and sheet-shaped soft magnetic powder are combined according to a specific mass ratio, and their particle size and loose density are controlled to form an absorbent material with high magnetic permeability. The absorbent tube sleeve is prepared through two kneading and extrusion processes.
It improves the magnetic permeability and mechanical properties of wave absorbing materials, enhances the anti-electromagnetic interference ability of wave absorbing products, and ensures the flat surface and efficient extrusion of the product.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of absorbing materials, and in particular to an absorbing material, an absorbing tube sleeve using the absorbing material, and a preparation method thereof. Background Art
[0002] Any electromagnetic phenomenon that may cause the performance of electronic devices, equipment or systems to degrade or even fail, or cause damage to living or inanimate matter is called electromagnetic interference (EMI). Almost every electronic device will generate electromagnetic interference signals to varying degrees, which may be radiated in the form of electromagnetic radiation or transmitted through current-carrying conductors such as power lines and cables. Almost all electronic devices are sensitive to interference signals generated by other electronic devices.
[0003] With the development of highly integrated electronic products, electromagnetic interference and electromagnetic compatibility between electronic components have gradually emerged and are becoming increasingly prominent. Electromagnetic interference between electronic components can have serious destructive effects on electrical and electronic equipment or systems, especially those containing semiconductor devices. Summary of the invention
[0004] In order to solve the electromagnetic interference problem existing between existing electronic products, the present invention provides an absorbing material, an absorbing tube sleeve using the same and a preparation method.
[0005] According to a first aspect of the present invention, there is provided an absorbing material, which comprises a spherical soft magnetic powder and a flaky soft magnetic powder. The mass ratio of the spherical soft magnetic powder to the flaky soft magnetic powder is 1:2.3-2.4. The particle size D50 of the spherical soft magnetic powder is 55-65 μm, and the particle size D50 of the flaky soft magnetic powder is 50-65 μm. The bulk density of the spherical soft magnetic powder is 2.3-2.6 g / cm 3 The bulk density of the flaky soft magnetic powder is 0.35~0.43 g / cm 3 .
[0006] Due to its high magnetic permeability and non-conductive properties, absorbing materials can directly absorb electromagnetic waves without generating eddy currents, reflecting electromagnetic waves, or causing secondary pollution to surrounding electronic components. Therefore, they are used in electronic components to eliminate electromagnetic interference. The absorbing material patches made of absorbing materials conform to the development trend of higher and higher integration of electronic products and more and more dense arrangement of electronic components.
[0007] The absorbing material commonly used in the existing absorbing material patch is soft magnetic powder that has been flaked. Compared with the spherical soft magnetic powder that has not been flaked, the mutual contact between the flaky soft magnetic powders is mainly surface contact, the contact area between the flaky soft magnetic powders is larger, the resistance is smaller, the magnetic permeability of the absorbing material is higher, and the anti-electromagnetic interference performance is better. Although the magnetic permeability of the flaky soft magnetic powder is high when used as an absorbing material, due to the surface contact between the flaky soft magnetic powders, when the absorbing material is used to prepare an absorbing product, the fluidity of the overall slurry will be deteriorated, affecting the normal extrusion of the absorbing material, and then affecting the mechanical properties of the absorbing product, and ultimately making it difficult for the prepared absorbing product to play a good role in anti-electromagnetic interference.
[0008] For the absorbing material using only spherical soft magnetic powder, since the spherical soft magnetic powder has not been processed into flakes, its magnetic permeability is low and it is difficult to meet the requirements of electronic products for the anti-electromagnetic interference performance of the absorbing material.
[0009] Compared with using only flaky soft magnetic powder or spherical soft magnetic powder as the wave absorbing material, the present invention combines spherical soft magnetic powder with a particle size D50 of 55-65 μm with spherical soft magnetic powder with a particle size D50 of 50-65 μm. The flaky soft magnetic powder with a particle size of 0.1 μm is compounded in a mass ratio of 1:2.3-2.4 as an absorbing material. The soft magnetic powders of different shapes and sizes are compounded in a specific mass ratio and the loose density of the spherical soft magnetic powder and the flaky soft magnetic powder is adjusted so that the two meet the above range, which has a good synergistic effect, is conducive to improving the compatibility of the spherical soft magnetic powder and the flaky soft magnetic powder, and makes the flaky soft magnetic powder and the spherical soft magnetic powder better contact each other, which is conducive to forming a good conductive network, so that the absorbing material has a higher magnetic permeability. When the absorbing material provided by the present invention is used to prepare an absorbing product, the flaky soft magnetic powder and the spherical soft magnetic powder can ensure the fluidity of the overall slurry when the particle size, mass ratio and loose density range are met, and the extrusion effect of the absorbing material is better, so that the surface formed by the absorbing material in the actual application process is more flat and smooth and the magnetic permeability is optimal, which not only improves the mechanical properties of the finally obtained absorbing product, but also enables the obtained absorbing product to have the characteristics of high magnetic permeability, and endows it with good anti-electromagnetic interference performance.
[0010] Preferably, the spherical soft magnetic powder and the flaky soft magnetic powder are independently selected from at least one of sendustine soft magnetic powder (Fe-Si-Al), iron-nickel soft magnetic powder (Fe-Ni), iron-chromium soft magnetic powder (FeCr), iron-silicon-chromium soft magnetic powder (FeSiCr), carbonyl iron soft magnetic powder and ferrite soft magnetic powder.
[0011] Preferably, the above-mentioned absorbing material further comprises ethylene-vinyl acetate copolymer (EVA).
[0012] Preferably, the ethylene-vinyl acetate copolymer (EVA) has a VA content of 30-45 wt %, and / or a melt index of the ethylene-vinyl acetate copolymer of 0.3-40 g / 10 min.
[0013] Using ethylene-vinyl acetate copolymer with a VA content of 30-45 wt% and a melt index of 0.3-40 g / 10min as the resin component in the absorbing material can improve the flexibility and transparency of the product formed during the application of the absorbing material.
[0014] Preferably, the above-mentioned absorbing material further comprises a coupling agent, and the coupling agent comprises at least one of an aminosilane coupling agent and an epoxysilane coupling agent.
[0015] By introducing a coupling agent into the absorbing material, the molecular structure of the coupling agent contains both an inorganic-philic group and an organic-philic group, which can act as a "bridge" between inorganic and organic substances, thereby improving the interface between them and further improving the performance of the absorbing material. In addition, the coupling agent used in this scheme is a silane coupling agent. In the presence of water, the alkoxy group in the silane coupling agent can be hydrolyzed to generate silanol groups, thereby enhancing the reactivity of the coupling agent with the surface of the inorganic absorbing material.
[0016] Preferably, the above-mentioned absorbing material further comprises a plasticizer and a roller-release mold release agent, the plasticizer comprises dioctyl phthalate (DOP), and the roller-release mold release agent comprises alkyd resins.
[0017] According to a second aspect of the present invention, there is provided an absorbing tube sleeve, the absorbing tube sleeve comprising the above-mentioned absorbing material.
[0018] In order to solve the problem of electromagnetic interference, absorbing material patches are usually attached to both sides of the product (such as chips or integrated circuits, etc.). Although sticking absorbing material patches on both sides can alleviate the degree of electromagnetic interference to a certain extent, there will still be varying degrees of electromagnetic leakage and electromagnetic entry around the product, which will seriously affect the performance of the product.
[0019] The absorbing tube sleeve provided by the present invention uses the absorbing material provided by the present invention, and has the characteristics of high magnetic permeability. The absorbing tube sleeve can be directly sleeved on the product used, effectively avoiding and solving the phenomenon of electromagnetic leakage and entry around the product, thereby achieving the purpose of anti-electromagnetic interference. In addition, in the process of preparing the absorbing material of the present invention into the absorbing tube sleeve by using the extrusion process, since the absorbing material is compounded by soft magnetic powders of different shapes and sizes according to a specific mass ratio, the absorbing material has a better extrusion effect, and the prepared absorbing tube sleeve has the characteristics of high structural strength, which can improve the durability of the absorbing tube sleeve in resisting electromagnetic interference.
[0020] Preferably, the above-mentioned absorbing tube sleeve is prepared by the following steps:
[0021] S1. The above-mentioned absorbing material is first mixed at 100-130°C to obtain a first mixture, the first mixture is cooled and crushed, and then mixed for a second time at 100-130°C, and a second mixture having a mesh size of 150-200 is obtained after cooling and crushing;
[0022] S2. Extruding the second mixed material at 100-160° C. to obtain an absorbing tube sleeve.
[0023] In the preparation method of the absorbing tube sleeve provided in the present scheme, firstly, the absorbing material provided by the present invention is mixed twice and the mixing temperature is controlled between 100 and 130° C., and the first mixture is cooled and crushed after the first mixing, which can reduce the risk of agglomeration of the absorbing material after the second mixing, make the mixing of the absorbing material more uniform, and improve the magnetic permeability of the absorbing material after mixing, so that the absorbing tube sleeve obtained by extrusion has better anti-electromagnetic interference properties. Secondly, the absorbing material is crushed after the second mixing so that the particle size of the second mixture is between 150 and 200 meshes, which is conducive to reducing the difficulty of rubber coating, allowing the second mixture to be extruded normally, and improving the production efficiency of the absorbing tube sleeve.
[0024] Preferably, in S1, the first mixing time is 1 to 1.5 hours, and / or the second mixing time is 1 to 1.5 hours.
[0025] Preferably, in S1, before the absorbing material is mixed for the first time, the absorbing material is mixed with aqueous ammonia, and the mass percentage of the aqueous ammonia is 25-26%.
[0026] Preferably, in S2, the extrusion speed is 15-20 r / min.
[0027] In the preparation process of the absorbing tube sleeve, by controlling the extrusion speed within the above range, it is not only beneficial to the continuous production and preparation of the absorbing tube sleeve, but also can make the shape of the finally prepared absorbing tube sleeve more regular and have better mechanical properties, thereby reducing the risk of deformation of the absorbing tube sleeve due to irregular shape during the subsequent cutting process.
[0028] Preferably, in S2, during the extrusion operation, the second mixed material is extruded in three stages, the extrusion temperature of the first stage is 140-160°C, the extrusion temperature of the second stage is 120-140°C, and the extrusion temperature of the third stage is 100-120°C.
[0029] During the two mixing and extrusion processes of the absorbing material, the temperature of each temperature zone is controlled within the above range, so as to further improve the shape regularity and mechanical properties of the absorbing tube sleeve, thereby reducing the risk of deformation of the absorbing tube sleeve due to irregular shape during the subsequent cutting process. DETAILED DESCRIPTION
[0030] The following is a further clear and complete description of the technical features in the technical solution provided by the present invention in conjunction with the specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] Treatment Group 1A
[0033] An absorbing tube sleeve is prepared by the following steps:
[0034] S1. The absorbing material is placed in an internal mixer and mixed for a first time at 130° C. for 1.5 hours to obtain a first mixture, and then the first mixture is cooled to room temperature, crushed, and heated to 130° C. again for a second mixing for 1.5 hours. After cooling, crushing and sieving, a second mixture with a mesh size between 150 and 200 is obtained;
[0035] The above-mentioned absorbing material includes the following components: 25 kg ethylene-vinyl acetate copolymer (EVA), 35 kg spherical sendust soft magnetic powder, 82 kg flake sendust soft magnetic powder, 600 g plasticizer dioctyl phthalate (DOP), 1200 g aminosilane coupling agent KH550, 150 g water, 150 g ammonia water (concentration of 30 wt%), 1350 g roll-off release agent stearic acid;
[0036] Among them, the content of ethyl acetate (VA) in EVA is 30 wt%, and the melt index of EVA is 0.3 g / 10min;
[0037] The particle size D50 of the spherical Sendust soft magnetic powder is 60 μm and the bulk density (AD value) is 2.4 g / cm 3 ;
[0038] The particle size D50 of the flaky sendust soft magnetic powder is 60 μm, and the bulk density (AD value) is 0.4 g / cm 3 ;
[0039] S2. Pour the second mixed material into a single screw extruder for extrusion to obtain an absorbing tube sleeve, wherein the die extrusion thickness of the single screw extruder is set to 0.5 mm, the die temperature of the single screw extruder is set to 130°C, and the second mixed material is extruded in three stages, the first stage extrusion temperature is 150°C, the second stage extrusion temperature is 130°C, and the third stage extrusion temperature is 110°C, which is abbreviated as three-stage temperature 150°C / 130°C / 110°C, and the extrusion speed is 18 r / min.
[0040] The treatment groups 2A-3A and the comparative groups 1A-8A of Example 1 were prepared with reference to the formula and method provided by the treatment group 1A of Example 1, and the formula of the absorbing material and the shape, particle size D50, AD value, and mass ratio of the flaky soft magnetic powder to the spherical soft magnetic powder were used as variables. The variables of the absorbing material in the absorbing tube sleeves of the treatment groups 1A-3A and the comparative groups 1A-8A of Example 1 are shown in Table 1. Except for the above differences, the materials, formula ratios, and preparation operations used in the treatment groups 2A-3A and the comparative groups 1A-8A were strictly consistent with those of the treatment group 1A.
[0041] Table 1 Variables involved in treatment groups 1A-4A and comparison groups 1A-4A in Example 1
[0042]
[0043] Treatment Group 4A
[0044] This treatment group provides an absorbing tube sleeve, and compared with Example 1, the difference in structure is that the absorbing material used in the preparation step S1 of the absorbing tube sleeve does not contain ammonia water and water. In addition to the above differences, the materials, formula ratios and preparation operations used in this treatment group are strictly consistent with those of the treatment group 1A of Example 1.
[0045] Comparative group 9A
[0046] This comparative group provides an absorbing tube sleeve, and compared with Example 1, the difference in structure is that in the absorbing material used in the preparation step S1 of the absorbing tube sleeve, an equal amount of spherical Sendust soft magnetic powder is used to replace the flake Sendust soft magnetic powder, that is, the absorbing material only contains spherical Sendust soft magnetic powder and does not contain flake Sendust soft magnetic powder. In addition to the above differences, the materials, formula ratios and preparation operations used in this comparative group are strictly consistent with those of the treatment group 1A of Example 1.
[0047] Control group 10A
[0048] This comparative group provides an absorbing tube sleeve, and compared with Example 1, the difference in structure is that in the absorbing material used in the preparation step S1 of the absorbing tube sleeve, an equal amount of flaky sendust soft magnetic powder is used to replace the spherical sendust soft magnetic powder, that is, the absorbing material only contains flaky sendust soft magnetic powder, and does not contain spherical sendust soft magnetic powder. In addition to the above differences, the materials, formula ratios and preparation operations used in this comparative group are strictly consistent with those of the treatment group 1A of Example 1.
[0049] Test Example 1
[0050] 1. Participants
[0051] In this test example, the absorbing tube sleeves prepared by the treatment groups 1A to 4A and the comparison groups 1A to 10A of Example 1 were used as test objects to conduct relevant performance tests.
[0052] 2. Test content
[0053] (1) Magnetic permeability
[0054] Magnetic permeability: The material was cut into rings with an inner diameter of 9 mm and an outer diameter of 16 mm on a mold and tested on an E4991B precision impedance analyzer.
[0055] (2) Density
[0056] Density: tested by Archimedes drainage method.
[0057] (3) Thickness
[0058] Place the product vertically (be careful not to tilt it) and measure it using a digital micrometer.
[0059] (4) Appearance
[0060] The visual method is used, and the distance between the naked eye and the object to be measured is within the range of 30~45 cm.
[0061] 3. Experimental results
[0062] Table 2 Performance test results of the absorber sleeves of treatment groups 1A~4A and comparison groups 1A~10A
[0063]
[0064] The performance test results of the absorbing tube sleeves prepared by the treatment groups 1A to 4A and the comparison groups 1A to 10A of Example 1 are shown in Table 2. By comparing the data, it can be seen that the particle size D50 of the spherical soft magnetic powder used in the absorbing material in the preparation process of the absorbing tube sleeves provided by the treatment groups 1A to 3A of Example 1 is between 55 and 65 μm, and the bulk density is between 2.3 and 2.6 g / cm 3The particle size of the flaky soft magnetic powder is between 50 and 65 μm, and the bulk density is between 0.35 and 0.43 g / cm 3 The mass ratio of spherical soft magnetic powder to flaky soft magnetic powder satisfies 1:2.3~2.4. The test results show that the magnetic permeability of the absorber sleeve provided by treatment groups 1A~3A is as high as 19.8~20.9 μ'@1MHz, and the density reaches 2.80 g / cm 3 The above, and the appearance is smooth, without particles, and without extrusion scratches. However, the particle size and / or mass ratio of the spherical soft magnetic powder and / or flaky soft magnetic powder in the absorbing material used in the preparation process of the absorbing tube sleeve provided by the comparison groups 1A~8A do not satisfy the above relationship, so that the magnetic permeability of the absorbing tube sleeve prepared by the comparison groups 1A~8A is lower than that of the treatment groups 1A~3A. The particle size of the spherical soft magnetic powder and flaky soft magnetic powder used in the comparison group 5A is too large, which makes the difficulty of adhesive coating in the preparation process of the absorbing tube sleeve increased, and it cannot be normally extruded. The particle size of the spherical soft magnetic powder and flaky soft magnetic powder used in the comparison group 6A is too small, so that the magnetic permeability of the finally prepared absorbing tube sleeve is significantly reduced. In the comparison group 7A, due to the increase of flaky soft magnetic powder, the fluidity of the overall slurry becomes worse, and it cannot be normally extruded. In the comparison group 8A, due to the increase of spherical soft magnetic powder used, the magnetic permeability of the finally prepared absorbing tube sleeve is lower.
[0065] Compared with Example 1, the absorbing material used in the preparation process of the absorbing tube sleeve provided by treatment group 4A does not contain ammonia water and water, and the magnetic permeability of the prepared absorbing tube sleeve is lower than that of Example 1. This is mainly because no ammonia water and water are added, and the aminosilane coupling agent therein is difficult to hydrolyze, so the interface effect between the soft magnetic powder and EVA and the reaction ability between the two are weak, which leads to the low magnetic permeability and poor mechanical properties of the prepared absorbing tube sleeve, and the rough surface and extrusion scratches.
[0066] Example 2
[0067] The treatment group 1B of Example 2 was strictly prepared according to the formula and method provided by the treatment group 1A of Example 1. The treatment groups 2B~3B of Example 2 were prepared with reference to the formula and method provided by the treatment group 1B of Example 2, and the VA content and melt index of EVA in the formula of the absorbing material were used as variables. The variables of the absorbing materials in the absorbing tube sleeves of the treatment groups 1B~3B of Example 2 are shown in Table 3. Except for the above differences, the materials, formula ratios and preparation operations used in the treatment groups 2B~3B were strictly consistent with those of the treatment group 1B.
[0068] Table 3 Variables involved in treatment groups 1B-3B and comparison groups 1B-4B in Example 2
[0069]
[0070] Test Example 2
[0071] 1. Participants
[0072] In this test example, the absorbing tube sleeves prepared by treatment groups 1B to 3B of Example 2 were used as test objects to conduct relevant performance tests.
[0073] 2. Test content
[0074] Refer to Test Example 1.
[0075] 3. Experimental results
[0076] Table 4 Performance test results of the absorbing tube sleeves of treatment groups 1B to 3B of Example 2
[0077]
[0078] The performance test results of the absorbing tube sleeves of treatment groups 1B~3B of Example 2 in this test example are shown in Table 4. Through data comparison, it can be seen that in the preparation process of the absorbing tube sleeves of treatment groups 1B~3B, ethylene-vinyl acetate copolymer with a VA content of 30~45 wt% and a melt index of 0.3~40 g / 10min is used as the resin component in the absorbing material. The absorbing tube sleeves formed during the extrusion of the absorbing material have high flexibility and transparency, and the prepared absorbing tube sleeves have the characteristics of high magnetic permeability.
[0079] Example 3
[0080] Treatment group 1C of Example 3 was prepared in strict accordance with the formula and method of treatment group 1A of Example 1. Treatment groups 2C to 3C of Example 3 and comparative groups 1C to 8C were prepared in accordance with the formula and method provided by treatment group 1C of Example 3, and the process parameters involved in the preparation steps of the absorbing tube sleeve were used as variables. The variables of treatment groups 2C to 3C and comparative groups 1C to 8C of Example 3 are shown in Table 5. Except for the above differences, the materials, formula ratios and preparation operations used in treatment groups 1C to 3C and comparative groups 1C to 8C were strictly consistent with those of treatment group 1C.
[0081] Table 5 Variables involved in treatment groups 1C to 3C and comparison groups 1C to 8C in Example 3
[0082]
[0083] Test Example 3
[0084] 1. Participants
[0085] In this test example, the absorbing tube sleeves prepared by the treatment groups 1C to 3C and the comparison groups 1C to 8C of Example 3 were used as test objects to conduct relevant performance tests.
[0086] 2. Test content
[0087] Refer to Test Example 1.
[0088] 3. Experimental results
[0089] Table 6 Performance test results of the absorbing tube sleeves of treatment groups 1C to 3C and comparison groups 1C to 8C of Example 3
[0090]
[0091] The performance test results of the absorbing tube sleeves of the treatment groups 1C to 3C and the comparison groups 1C to 8C of Example 3 in this test example are shown in Table 6.
[0092] Through data comparison, it can be seen that the temperature of the two mixings in the preparation process of the absorbing tube sleeves provided by treatment groups 1C~3C is between 100~130℃, the mesh number of the second mixture obtained after two mixings is between 150~200 mesh, and the extrusion temperature is between 100~160℃. The magnetic permeability of the absorbing tube sleeves finally obtained is as high as 20μ'@1MHz, and the absorbing tube sleeves have a smooth appearance, no particles, and no extrusion scratches.
[0093] Compared with treatment group 1C, the mixing temperature of the absorbing material used in the preparation process of the absorbing tube sleeve provided by comparison group 1C is 90°C. Due to the low mixing temperature, the softening point of each material in the absorbing material is just reached, and normal mixing cannot be performed, and the mixing of the soft magnetic powder and other components such as EVA in the absorbing material is very uneven; the mixing temperature of the absorbing material used in the preparation process of the absorbing tube sleeve provided by comparison group 2C is 150°C. Although normal mixing can be performed and the obtained absorbing tube sleeve also has a high magnetic permeability, the mechanical properties of the absorbing tube sleeve will deteriorate due to the excessively high mixing temperature, and the aging phenomenon will occur prematurely; comparison group 3C In the preparation process of the provided absorbing material, the mesh number of the second mixture obtained after the absorbing material is mixed twice is between 50 and 100 meshes. Since the mesh number of the second mixture is too small and the particle size of the second mixture is too large, the difficulty of EVA coating the soft magnetic powder is greatly increased during the mixing process, and normal extrusion is impossible. In the preparation process of the absorbing material provided by the comparison group 4C, the mesh number of the second mixture obtained after the absorbing material is mixed twice is between 200 and 300 meshes. Since the mesh number of the second mixture is too large and the particle size of the second mixture is too small, the magnetic permeability and density of the prepared absorbing tube sleeve are slightly lower than those of the treatment group 1C.
[0094] Compared with treatment group 1C, the die head temperature and the three-stage extrusion temperature of the single-screw extruder of the absorbing material provided by comparison group 5C were too high during the preparation process, which would result in the product being unable to cool down within the limited length of the production line, and the product being irregular in shape and easily deformed during cutting; the die head temperature and the three-stage extrusion temperature of the single-screw extruder of the absorbing material provided by comparison group 6C were too low during the preparation process, which would easily result in the discharge of the die head of the single-screw extruder being easily blocked during extrusion, and the absorbing tube sleeve could not be produced continuously; the extrusion speed of the absorbing material provided by comparison group 7C was 25 r / min during the preparation process, and due to the extrusion speed being too fast, the product being unable to cool down within the limited length of the production line, and the product being irregular in shape and easily deformed during cutting; the extrusion speed of the absorbing material provided by comparison group 8C was 10 r / min during the preparation process, and due to the extrusion speed being too slow, the discharge of the die head of the single-screw extruder being easily blocked during extrusion, and the absorbing tube sleeve could not be produced continuously.
[0095] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. A wave absorbing tube sleeve, characterized in that: The material of the absorbing tube sleeve includes absorbing material, and the absorbing material includes spherical soft magnetic powder, flaky soft magnetic powder and ethylene-vinyl acetate copolymer. The mass ratio of the spherical soft magnetic powder to the flaky soft magnetic powder is 1:2.3-2.
4. The particle size D50 of the spherical soft magnetic powder is 55-65 μm, and the particle size D50 of the flaky soft magnetic powder is 50-65 μm; The bulk density of the spherical soft magnetic powder is 2.3-2.6 g / cm 3 The bulk density of the flaky soft magnetic powder is 0.35-0.43 g / cm 3 ; The ethylene-vinyl acetate copolymer has a ethyl acetate content of 30 to 45 wt %, and / or the ethylene-vinyl acetate copolymer has a melt index of 0.3 to 40 g / 10 min; The absorbing tube sleeve is prepared by the following steps: S1. The absorbing material is mixed with aqueous ammonia and kneaded for the first time at 100-130° C. to obtain a first mixture, the first mixture is cooled and crushed, and then kneaded for the second time at 100-130° C., and a second mixture having a mesh size between 150 and 200 is obtained after cooling and crushing; The mass percentage of the ammonia water is 25-26%; S2. Extruding the second mixture at 100-160° C. to obtain the absorbing tube sleeve; In S2, during the extrusion operation, the extrusion speed is 15-20 r / min, the second mixed material is extruded in three stages, the extrusion temperature of the first stage is 140-160°C, the extrusion temperature of the second stage is 120-140°C, and the extrusion temperature of the third stage is 100-120°C.
2. The absorbing tube sleeve according to claim 1, characterized in that: The spherical soft magnetic powder and the flaky soft magnetic powder are independently selected from at least one of sendustine soft magnetic powder, iron-nickel soft magnetic powder, iron-chromium soft magnetic powder, iron-silicon-chromium soft magnetic powder, carbonyl iron soft magnetic powder and ferrite soft magnetic powder.
3. The absorbing tube sleeve according to claim 1, characterized in that: The absorbing material further comprises a coupling agent, and the coupling agent comprises at least one of an aminosilane coupling agent and an epoxysilane coupling agent.
Citation Information
Patent Citations
Wave-absorbing material, wave-absorbing coiled material capable of being coiled continuously and preparation method
CN105733084A
Soft magnetic wave-absorbing injection molding material and preparation method thereof
CN117700974A